TERMOTOLERÂNCIA E DESENVOLVIMENTO LARVAL DE LUCILIA CUPRINA (WIEDEMANN) (DIPTERA: CALLIPHORIDAE) - Lôbo Doni, Giovanna; Castro de Paula Silva, Michele; Cardoso Videira , Thayná; Eduardo Lima Junior, Sidnei; Fernando Antonialli Junior, William (ANAIS DO ENIC, 2026)
-